Penetapan Selling Price Set Menu Pada Event New Year Previere Lounge Di Grand Dafam Signature Surabaya - Aulia Salsabila Az-zahra; Niken Purwidiani; Ila Huda Puspita; Lilis Sulandari (Pusat Riset dan Inovasi Nasional, 2023)
Food cost and selling price in the industrial world such as restaurants in hotels are very important in order to control production costs in processing food ingredients. The method used in this research is descriptive qualitative. Data collection techniques in the form of interviews, observation and documentation using inductive qualitative data analysis methods. Determination of selling price on the set menu through the calculation of market segmentation, competitor analysis, raw materials, and company standards owned. Food cost generated by each dish item has an important role in determining the selling price because it is very influential. Cost of package is the biggest determinant of costs incurred from 2 kinds of main dishes served. The results of this study indicate the determination of the selling price of the new year menu set using the mark-up pricing method based on standard calculations from the company. Strategy and determination of the target market as the main thing that must be considered, with a survey of several competitors including composition and price will be known how feasible the dish competes in the market.